Association of race and ethnicity with mortality in adults with SLE: a systematic literature review and meta-analysis - Sam Norton; Chris Wincup; Patrick Gordon; Kate Bramham; James Galloway; Zijing Yang; Samir Patel; Maryam Adas; Deepak Nagra; Mark Russell (Lupus Science and Medicine)
Objectives Ethnicity and health outcomes are intrinsically interrelated, although mechanisms are complex. SLE is a disease with higher incidence in Asian, Black, Hispanic and Indigenous populations than in White populations. SLE is associated with premature mortality, but it is unclear if ethnicity impacts on health outcomes as studies are frequently underpowered. We aimed to describe the association between SLE and mortality across different racial and ethnic groups using meta-analysis.Methods We identified studies of adults with SLE that reported mortality, stratified by racial and ethnic group, through a systematic literature review. We used a pairwise meta-analysis to determine the pooled odds ratio (OR) of death for those from underserved groups compared with those of White race and ethnicity.Results Thirty-seven studies, comprising 85 578 patients with SLE, were included. Mortality was higher in Black patients (OR 1.30 (95% CI 1.16 to 1.46)) and Indigenous patients (OR 1.47 (95% CI 1.11 to 1.94)), while Asian and Hispanic patients showed no significant differences compared with White patients with SLE. Seventy per cent of included studies were conducted in the USA and when excluded, the significant difference in mortality between Black and White individuals with SLE was no longer seen (OR 0.84 (95% CI 0.54 to 1.31)).Conclusion Overall, patients with SLE from Black or Indigenous racial and ethnic groups had higher mortality than those of White race and ethnicity. We observed no significant association in the mortality of Black patients compared with White patients from non-USA cohorts, but a scarcity of data outside of the USA was highlighted. We promote caution in the use of race and ethnicity as a factor in determining mortality risk until more generalisable data are available.PROSPERO registration number CRD42023379034.